152k views
5 votes
Can you please tell me how to solve this????

Can you please tell me how to solve this????-example-1

1 Answer

0 votes

Answer:

-2

Explanation:

You have to simplify numerator and denominator through factoring. The you should get an expression involving only a + b which is given as -2

Take numerator

a^2-b^2-12b-36

Factor

-b^2-12b-36


= - (b^2 + 12b + 36)\\\\= -(b+6)^2

So numerator becomes

a^2-\left(b+6\right)^2

Apply difference of squares formula:
\displaystyle x^2-y^2=\left(x+y\right)\left(x-y\right)


\mathrm{with\;} x^2 == > a^2, and y^2 == > (b + 6)^2


\implies a^2-\left(b+6\right)^2 \\== \left(a+\left(b+6\right)\right)\left(a-b-6\right)

Denominator

a^2-6a-b^2-6b

can be factored as follows


a^2-b^2 = (a + b) (a -b)

-6a-6b = -6\left(a+b\right)

So denominator becomes

\left(a+b\right)\left(a-b\right)+-6\left(a+b\right)

Factor out common term (a+b) to get

\left(a+b\right)\left(a-b-6\right)

So the original expression with Numerator and denominator


\displaystyle =(\left(a+b+6\right)\left(a-b-6\right))/(\left(a+b\right)\left(a-b-6\right))
Cancel the common factor (a-b-6) to get

\displaystyle (a+b+6)/(a+b)

Since a + b = -2, plug in this value of (a+b) in both numerator and denominator to get

\displaystyle (-2 + 6)/(-2)

\displaystyle = - 2

Answer: -2





User Jules Copeland
by
5.0k points